Effect of Aerobic Training with Aqueous Allium sativum L on IL-17, IL-22 Expression and Insulin Resistance in Diabetic Rats - Elnaz Sadeghpour Firozabadi; Ahmad Abdi; Asieh Abbassi Daloii (فیزیولوژی ورزش و فعالیت بدنی)
Background and Purpose: There is now mounting evidence that pro-inflammatory pathways, which are mediated by T cells (that secrete IL-17 and IL-22), play a critical role in metabolic control. The aim of this study was to examine the effect of aerobic training along with aqueous extract of Garlic (Allium sativum L.) on relative expression of IL-17, IL-22 and insulin resistance in streptozotocin-diabetic rats.Materials and Methods: In this experimental study, 40 male Wistar rats (age five weeks and weight 162.12 ± 15.24 g) were obtained from the Pasteur Institute and transferred to the laboratory. After transferring the rats to the laboratory, inducing diabetes and familiarizing them with exercise on a rodent treadmill, they were randomly divided into five groups: Control-Normal (CN), Diabetes (DM), Diabetes-Training (TDM), Diabetes-Garlic (GDM) and Diabetes-Training-Garlic (TGDM). Diabetes was induced in the rats by the intraperitoneal administration of a single dose of Streptozotocin (60 mg/kg). Blood glucose of 250 mg/dL was the criterion for diabetic rats. Training groups have performed an aerobic running program (at 10-18 m/min, 10-40 min/day, and five days/week) on a motor-driven treadmill for eight weeks. A dose of one ml of garlic extract /100 g body weight (about 0.4 grams per 100 grams of body weight) was orally administered daily to rats. The expression of IL-17 and IL-22 was measured by RT-PCR method. After estimating fasting glucose and insulin levels, HOMA-IR index was used to evaluate insulin resistance. Data were analyzed using ANOVA and Pearson's correlation coefficient at P < 0.05. Results: The expression of IL-17 (P = 0.0001), IL-22 (P = 0.0001) and HOMA-IR level (P = 0.0001) increased in DM groups compared to CN group. IL-17, IL-22 and HOMA-IR was significantly lower in TDM (respectively, P = 0.008, P = 0.040, P = 0.0001), GDM (respectively, P = 0.017, P = 0.044, P = 0.0001) and TGDM (respectively, P= 0.0001, P = 0.0001, P = 0.0001) groups than in DM group. Also, IL-17 and IL-22 in the TGDM group lower than TDM (respectively, P = 0.045, P= 0.041) and GDM (respectively, P = 0.023, P = 0.038) groups. A positive correlation was observed between HOMA-IR and IL-17 (P = 0.0001) and IL-22 (P = 0.001).Conclusions: The findings of the present study show that probably the increase in the relative expression of IL-17 and IL-22 with the induction of diabetes is associated with an increase in insulin resistance. Decreased IL-17 and IL-22 expression adipose tissue followed by aerobic training and aqueous garlic extract were associated with decreased HOMA-IR in diabetic rats. In addition, the combination of aerobic exercise with garlic extract had synergistic effects and reduced inflammation and HOMA-IR compared to each alone. Since diabetics are constantly exposed to inflammation and according to the reduction of IL-17 and IL-22 following aerobic exercise and consumption of garlic extract, the use of these two could possibly be of therapeutic importance for T2DM patients.